2017
DOI: 10.1159/000478706
|View full text |Cite
|
Sign up to set email alerts
|

Pure Testicular Seminoma with Non-Pathologic Elevation of Alpha Fetoprotein: A Case Series

Abstract: Background: Pure testicular seminoma does not express alpha fetoprotein (AFP). However, seminoma patients with mildly elevated serum AFP levels are increasingly reported. As this finding may prompt unwarranted treatment measures, we reviewed our experience with AFP levels in seminoma. Patients and Methods: We retrospectively registered AFP levels in 254 consecutive seminoma patients, and in 196 male controls with non-malignant diseases. In those with elevated AFP levels, we re-examined the orchiectomy specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…However, rates of 30–31% had been reported likewise [47, 48]. AFP was expressed in 60% of nonseminomas, while only isolated patients with seminoma had unspecific elevations of this marker [49]. The expression rate of LDH was also significantly higher in nonseminomas, which represents an unexpected finding [50, 51].…”
Section: Discussionmentioning
confidence: 96%
“…However, rates of 30–31% had been reported likewise [47, 48]. AFP was expressed in 60% of nonseminomas, while only isolated patients with seminoma had unspecific elevations of this marker [49]. The expression rate of LDH was also significantly higher in nonseminomas, which represents an unexpected finding [50, 51].…”
Section: Discussionmentioning
confidence: 96%
“…AFP involves a considerably longer half-life of 5–7 days [24-26]. Particularly in CS1 patients with elevated AFP levels, it is sometimes inconvenient to wait for appropriate marker decline to be sure about the stage 1 condition [27]. A half-life of less than 24 h, as found for miR-371a-3p, thus represents a highly useful feature of a serum tumour marker [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, as for patients with a persistently elevated AFP level, a comprehensive evaluation is required to identify the cause. In our literature review, at least five cases in nonseminomatous GCTs and six cases in seminoma received additional interventions based on a false elevated AFP level [18,26,32,37]. Albany and Einhorn also suggested that patients with an elevated AFP level should not receive salvage chemotherapy unless there is a sustained rise in AFP [48].…”
Section: Discussionmentioning
confidence: 95%
“…In some cases, no etiology was reported, especially in seminoma [31,[33][34][35][36]. Dieckmann et al reported approximately 2% of pure seminoma patients had a non-pathologic AFP elevation, and this proportion was not different from that of controlled patients with non-malignant urologic diseases [32]. In addition, AFP can be expressed in other malignancies, of which HCC is the most frequent, and some nontumor diseases, such as Fanconi anemia and ataxiatelangiectasia [39,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation